An Ideal PPAR Response Element Bound to and Activated by PPARα - Tzeng, John; Byun, Jaemin; Park, Ji Yeon; Yamamoto, Takanobu; Schesing, Kevin; Tian, Bin; Sadoshima, Junichi; Oka, Shin-ichi (PLOS ONE, 2015)
Peroxisome proliferator-activated receptor-α (PPARα), a nuclear receptor, plays an important role in the transcription of genes involved in fatty acid metabolism through heterodimerization with the retinoid x receptor (RXR). The consensus sequence of the PPAR response element (PPRE) is composed of two AGGTCA-like sequences directionally aligned with a single nucleotide spacer. PPARα and RXR bind to the 5’ and 3’ hexad sequences, respectively. However, the precise sequence definition of the PPRE remains obscure, and thus, the consensus sequence currently available remains AGGTCANAGGTCA with unknown redundancy. The vague PPRE sequence definition poses an obstacle to understanding how PPARα regulates fatty acid metabolism. Here we show that, rather than the generally accepted 6-bp sequence, PPARα actually recognized a 12-bp DNA sequence, of which the preferred binding sequence was WAWVTRGGBBAH. Additionally, the optimized RXRα hexad binding sequence was RGKTYA. Thus, the optimal PPARα/RXRα heterodimer binding sequence was WAWVTRGGBBAHRGKTYA. The single nucleotide substitution, which reduces binding of RXRα to DNA, attenuated PPARα-induced transcriptional activation, but this is not always true for PPARα. Using the definition of the PPRE sequence, novel PPREs were successfully identified. Taken altogether, the provided PPRE sequence definition contributes to the understanding of PPARα signaling by identifying PPARα direct target genes with functional PPARα response elements.